Examining the Impact of Nitrous Acid Chemistry on Ozone and PM over the Pearl River Delta Region - Rui Zhang; Golam Sarwar; Jimmy C. H. Fung; Alexis K. H. Lau; Yuanhang Zhang (Advances in Meteorology)
The impact of nitrous acid (HONO) chemistry on regional ozone and particulate matter in Pearl River Delta region was investigated using the community multiscale air quality (CMAQ) modeling system and the CB05 mechanism. Model simulations were conducted for a ten-day period in October 2004. Compared with available observed data, the model performance for NOx, SO2, PM10, and sulfate is reasonably good; however, predictions of HONO are an order of magnitude lower than observed data. The CB05 mechanism contains several homogenous reactions related to HONO. To improve the model performance for HONO, direct emissions, two heterogeneous reactions, and two surface photolysis reactions were incorporated into the model. The inclusion of the additional formation pathways significantly improved simulated HONO compared with observed data. The addition of HONO sources enhances daily maximum 8-hour ozone by up to 6 ppbV (8%) and daily mean PM2.5 by up to 17 ug/m3 (12%). They also affected ozone control strategy in Pearl River Delta region.